Alloy for RTB permanent magnets and method for producing RTB permanent magnets
Patent Information
- Application Number
- JP2021058801
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-03-30
Smart Images

Figure 0007645120000003 
Figure 0007645120000004 
Figure 0007645120000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an alloy for an RTB permanent magnet and a method for producing an RTB permanent magnet. [Background technology]
[0002] Patent Document 1 describes an invention related to alloy flakes for rare earth magnets, characterized in that the thickness and surface roughness are within specific ranges. By controlling the surface roughness of the casting roll surface to fall within a specific range, the fine R-rich phase region in the alloy flakes for rare earth magnets is reduced, improving the magnetic properties.
[0003] Patent Document 2 describes an invention relating to a method for producing rare earth-containing alloy flakes, characterized in that the shape of the casting surface of a rotating cast roll is a specific shape and the surface roughness of the casting surface of the rotating cast roll is within a specific range. The RTB alloy flakes produced by this production method have a reduced fine R-rich phase region and are excellent in homogeneity.
[0004] Patent Document 3 describes an invention relating to a raw material alloy for RTB magnets, characterized in that the volume ratio of the region where secondary dendrite arms are formed is within a specific range. The formation of secondary dendrite arms refines the structure, and therefore the coercive force of an RTB sintered magnet obtained using this raw material alloy for RTB magnets is improved. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-188006 A [Patent Document 2] JP 2004-181531 A [Patent Document 3] International Publication No. 2014 / 156181 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an alloy for an RTB permanent magnet that can be used to produce an RTB permanent magnet with improved magnetic properties. [Means for solving the problem]
[0007] In order to achieve the above object, the present invention provides an alloy for an RTB type permanent magnet having R, T and B, where R is a rare earth element, T is a transition metal element, and B is boron, and the area ratio of the non-columnar crystal structure in a cross section is 1.0% or more and 30.0% or less.
[0008] The area ratio of the non-columnar crystal structure may be 4.0% or more and 30.0% or less.
[0009] The non-columnar crystal structure may contain a chilled crystal structure, and the area ratio of structures other than the chilled crystal structure in the non-columnar crystal structure may be 50% or more.
[0010] The content of R may be 29.0 mass % or more and 33.5 mass % or less, and the content of B may be 0.70 mass % or more and less than 0.96 mass %.
[0011] The method for producing an RTB permanent magnet according to the present invention includes a step of pulverizing the above-mentioned alloy for an RTB permanent magnet. [Brief description of the drawings]
[0012] [Figure 1] This is a backscattered electron image of normal tissue. [Diagram 2] This is a backscattered electron image of chill crystal structure. [Diagram 3] This is a backscattered electron image of a structure containing fine dots of R-rich phase. [Figure 4] This is a backscattered electron image of a structure containing fine dots of R-rich phase. [Diagram 5] This is a backscattered electron image of a structure containing dot-like R-rich phases. [Figure 6]It is a backscattered electron image of a tissue containing a fine linear R-rich phase. [Figure 7] It is a backscattered electron image of a tissue containing a fine linear R-rich phase. [Figure 8] It is a backscattered electron image of a tissue containing a large dot-like R-rich phase. [Figure 9] It is a backscattered electron image of an evaluation sample partitioned by compartments. [Figure 10] It is a luminance histogram in one compartment of FIG. 9. [Figure 11] It is a graph showing the difference in the peak position and σ of the luminance histogram by tissue. [Figure 12] It is a schematic diagram of a casting device.
Embodiments for Carrying Out the Invention
[0013] Hereinafter, the present invention will be described based on the embodiments shown in the drawings.
[0014] <Microstructure of an alloy for an R-T-B type permanent magnet> The alloy for an R-T-B type permanent magnet according to the present embodiment has R, T, and B, and is an alloy for an R-T-B type permanent magnet in which R is a rare earth element, T is a transition metal element, and B is boron, and the area ratio of the non-columnar crystal structure in the cross section is 1.0% or more and 30.0% or less.
[0015] Generally, an alloy for an R-T-B type permanent magnet has a columnar crystal having an R2T 14 main phase having a B-type crystal structure and an R-rich phase having a higher R content than the main phase.
[0016] In the cross section of the RTB permanent magnet alloy, as shown in the backscattered electron image of FIG. 1, a clear difference can be confirmed between the main phase 11 and the R-rich phase 13, and the majority of the R-rich phase 13 is a structure 7 (hereinafter referred to as normal structure 7) in which the shape of the linear R-rich phase is the majority. Most of the main phase 11 contained in the normal structure 7 is columnar. In the normal structure 7, the spacing between the linear R-rich phases (hereinafter referred to as linear R-rich phases) is 2 μm or more on average. Furthermore, the normal structure 7 is a structure in which primary dendrites extend in the direction of solidification of the alloy, in other words, mainly in the thickness direction of the alloy.
[0017] In addition to the normal structure 7, RTB permanent magnet alloys also include structures that include a main phase that is not columnar. A main phase that is not columnar is called a non-columnar crystal, and a structure that includes non-columnar crystals is called a non-columnar crystal structure. A non-columnar crystal structure is a structure in which the primary dendrites do not necessarily extend in the direction of solidification of the alloy.
[0018] The non-columnar crystal structures contained in RTB permanent magnet alloys are classified into six types when a structure 1a and a structure 1b are distinguished from each other as described below. The six types of non-columnar crystal structures are explained below with reference to drawings (backscattered electron images).
[0019] Figure 2 includes chilled crystal structure 1, which includes structures 1a and 1b. Structure 1a is more different from normal structure 7 than structure 1b. In structure 1a, no clear difference is seen between the main phase and the R-rich phase. The brightness of structure 1a in a backscattered electron image is intermediate between that of the main phase and the R-rich phase. Furthermore, the variation in shading in a backscattered electron image of structure 1a is smooth.
[0020] Structure 1b is closer to normal structure 7 than structure 1a. However, structure 1b shows no clear difference between the main phase and the R-rich phase. The brightness of structure 1b in the backscattered electron image is intermediate between that of the main phase and the R-rich phase. Furthermore, the variation in shading in the backscattered electron image of structure 1b is smooth. Also, unlike structure 1a, structure 1b partially contains linear R-rich phases.
[0021] In the following description, when simply referring to chill crystal structures, no distinction is made between structure 1a and structure 1b.
[0022] 3 and 4 include a fine dot-like R-rich phase-containing structure 3 (hereinafter, sometimes referred to as structure 3). Different alloy pieces are observed in Figs. 3 and 4. In structure 3, a clear difference is observed between the main phase and the R-rich phase. However, compared to the normal structure 7 shown in Fig. 1, in structure 3, the R-rich phase aggregates in dots and is excessively dense. Furthermore, compared to the dot-like R-rich phase-containing structure 4 described below, the dot-like R-rich phase is finer.
[0023] For example, the dot-like R-rich phases contained in the structure 3 may have a size of 0.3 to 1.5 μm in terms of circle equivalent diameter, and the number of dot-like R-rich phases per unit area may be 0.25 pieces / μm 2 It may be more than that.
[0024] Furthermore, structure 3 can be cut into sections where the circle equivalent diameter and density of the dot-like R-rich phase are subtly different locally. The actual cut state is shown by dotted lines in Figure 4. The cut polygonal regions may have a long axis of 10 μm or more and 120 μm or less, and a short axis of 5 μm or more and 80 μm or less. The long axis refers to the longest distance between two parallel lines that contact the polygon from both sides, and the short axis refers to the shortest distance between two parallel lines that contact the polygon from both sides.
[0025] FIG. 5 includes a dot-like R-rich phase-containing structure 4 (hereinafter, sometimes referred to as structure 4). Structure 4 has a larger dot-like R-rich phase itself than structure 3. Furthermore, in the portion where the dot-like R-rich phase aggregates, a phase darker than the main phase exists.
[0026] 6 and 7 include a microstructure 5 containing fine linear R-rich phases (hereinafter, sometimes referred to as structure 5). Different alloy pieces are observed in Figs. 6 and 7. In structure 5, a clear difference is observed between the main phase and the R-rich phase. However, in structure 5, the linear R-rich phases are thinner and excessively denser than in the normal structure 7 shown in Fig. 1.
[0027] For example, the linear R-rich phases contained in the structure 5 may have a length of 4 to 125 μm, a width of 0.3 to 10 μm, and an interval between the linear R-rich phases of 1.0 to 1.8 μm.
[0028] Furthermore, the structure 5 can be cut into portions where the length, width, and density of the linear R-rich phase are subtly different locally. The actual cut state is shown by dotted lines in Fig. 7. The cut polygonal regions may have a major axis of 30 μm or more and 200 μm or less and a minor axis of 5 μm or more and 150 μm or less.
[0029] FIG. 8 includes a large dot-like R-rich phase-containing structure 6 (hereinafter, sometimes referred to as structure 6). In structure 6, the R-rich phase is aggregated to a large extent. The brightness of the main phase around the aggregated R-rich phase is slightly higher. Also, linear R-rich phases may be sandwiched between the large aggregated R-rich phases.
[0030] The seven normal structures and the six types of non-columnar crystal structures described above can be visually distinguished from backscattered electron images of the cross sections of RTB permanent magnet alloys.
[0031] <Calculation method for area ratio of non-columnar crystal structure> In this embodiment, the area ratio of the non-columnar crystal structure in the cross section of the RTB permanent magnet alloy is calculated by using brightness analysis of a backscattered electron image. The brightness analysis method will be described below.
[0032] First, in preparation for the brightness analysis, the brightness and contrast of the electron microscope are adjusted.
[0033] First, an alloy plate for an RTB permanent magnet to be used as a standard sample is prepared. The alloy plate for an RTB permanent magnet may be used as is, or a heat-treated plate obtained by subjecting the alloy plate for an RTB permanent magnet to heat treatment may be used. By carrying out the heat treatment, the process of bringing only the main phase 11 into the field of view of the electron microscope becomes easier. As a result, it becomes easier to adjust the brightness and contrast of the electron microscope. When carrying out the heat treatment, there is no particular limit to the heat treatment time and temperature. For example, the heat treatment is carried out at 800 to 1000°C for 30 to 120 minutes.
[0034] Next, Ni thin plate, Cu thin plate and Zn thin plate are prepared, and RTB permanent magnet alloy plate, Ni thin plate, Cu thin plate and Zn thin plate are embedded in embedding resin for electron microscope observation. At this time, the plates are arranged so that the cross sections parallel to the thickness direction are lined up, and a standard sample is prepared. At this time, there is no particular restriction on the type of thin plate other than the RTB permanent magnet alloy plate, and at least two types of thin plate are sufficient. The luminance peak position of each metal and the difference between the luminance peak positions of each metal described later may be appropriately set depending on the type of thin plate. In the following description, a case where Ni thin plate, Cu thin plate and Zn thin plate are used will be described.
[0035] Next, the cross section of the standard sample is mirror-polished and gold is vapor-deposited.
[0036] Next, the standard sample is set in the electron microscope. The imaging mode is backscattered electron imaging, with a pixel count of 1280 x 960 pixels. There are no particular limitations on the magnification, but the magnification should be such that the Ni thin plate, Cu thin plate, and Zn thin plate are in the same field of view.
[0037] Next, the field of view is shifted so that the Ni thin plate, the Cu thin plate, and the Zn thin plate are in the same field of view in that order.
[0038] Next, a luminance histogram is created with 256 gradations, with the minimum luminance being 0 and the maximum luminance being 255, and the brightness is adjusted so that the position of the Cu luminance peak is about 150 (145 to 155). Furthermore, the contrast is adjusted so that the difference between the position of the Ni luminance peak and the position of the Cu luminance peak is about 55 (45 to 65), and the difference between the position of the Cu luminance peak and the position of the Zn luminance peak is about 45 (35 to 55). When adjusting the contrast, the brightness is adjusted supplementarily as necessary to maintain the position of the Cu luminance peak at about 150.
[0039] Next, while maintaining the contrast, the field of view of the electron microscope is moved to a position where the RTB permanent magnet alloy plate is located. Then, the magnification is increased so that the white phase (R-rich phase 13) does not appear in the field of view and only the main phase 11 appears in the field of view. The magnification may be up to about 10,000 times. Furthermore, the brightness is adjusted so that the peak position of the brightness histogram is about 110 (105 to 115). Finally, the standard sample is collected from the electron microscope.
[0040] Next, the method of luminance analysis will be described.
[0041] First, prepare an RTB permanent magnet alloy for brightness analysis. Next, process the alloy so that its cross section can be observed, and prepare an evaluation sample. Multiple evaluation samples may be prepared and the results obtained may be averaged.
[0042] Next, the imaging mode is set to a reflected electron image, and the observation range is set at a magnification of 350 and a pixel count of 1280 × 960 pixels. Note that with the above magnification and pixel count, the observation range is 360 μm × 270 μm.
[0043] Next, the portion of the evaluation sample included in the above observation range is divided into sections at regular intervals. There is no particular limit to the size of each section, but it may be, for example, 40 pixels or more and 60 pixels or less. Figure 9 shows an image in which the cross section of the evaluation sample was actually observed and divided into sections with a size of 50 pixels. A cross section parallel to the thickness direction of the RTB permanent magnet alloy was observed, and the size of the image in Figure 9 is 1280 pixels (= 360 μm) horizontally and 960 pixels (= 270 μm) vertically for the entire image in Figure 9.
[0044] Next, a luminance histogram is created for each section. For example, Figure 10 shows the result of creating a luminance histogram for the seventh section from the top and the third section from the left in Figure 9. Then, the peak position and standard deviation (σ) of the luminance histogram are obtained for each section.
[0045] The present inventors have newly found the following. A section in which the peak position of the brightness histogram is 130 or more and 200 or less, and σ is 20 or more and 40 or less, can be regarded as a non-columnar crystal structure. The ratio of the number of sections in which the peak position of the brightness histogram and σ are within the above ranges relative to all sections can be regarded as the area ratio of the non-columnar crystal structure. An RTB permanent magnet manufactured using an alloy for an RTB permanent magnet in which the area ratio of the non-columnar crystal structure is 1.0% or more and 30.0% or less has good magnetic properties. In particular, it has been found that when the area ratio is 1.0% or more, HcJ at high temperatures tends to be high. It has also been found that when the area ratio is 30.0% or less, Hk / HcJ at room temperature tends to be high. It has been found that the area ratio of the non-columnar crystal structure is preferably 4.0% or more and 30.0% or less.
[0046] Furthermore, a section in which the peak position of the brightness histogram is between 130 and 200 and σ is between 30 and 40 can be regarded as a structure other than the chilled crystal structure in the non-columnar crystal structure. It was also found that the area ratio of the structure other than the chilled crystal structure in the non-columnar crystal structure may be 50% or more, preferably 85% or more and 95% or less, and more preferably 87% or more and 91% or less.
[0047] The relationship between the brightness histogram and the structure of the alloy for RTB permanent magnets will be further explained below. The inventors have found that the magnetic properties of RTB permanent magnets made from alloys for RTB permanent magnets in which the area ratio of the non-columnar crystal structure is within a predetermined range are good. However, the distinction between the normal structure and the non-columnar crystal structure by visually observing the backscattered electron image depends on the subjective judgment of the person making the measurement, and therefore the results may differ depending on the person making the measurement.
[0048] The inventors of the present invention considered that if the area ratio of the non-columnar crystal structure is calculated using brightness analysis, the area ratio of the non-columnar crystal structure independent of the person who performs the measurement can be calculated. For this purpose, the inventors of the present invention observed the cross sections of many RTB permanent magnet alloys. Then, the backscattered electron images of the cross sections were visually observed, and the structures were classified into normal structures and six types of non-columnar crystal structures. Then, the positions of the peaks and the tendency of σ were observed when creating a brightness histogram for each structure.
[0049] As a result, it was found that most of the brightness histograms of the sections with non-columnar crystal structure had peak positions between 130 and 200, and σ between 20 and 40. In contrast, it was found that most of the brightness histograms of the sections with normal structure had peak positions and / or σ outside the above ranges. The brightness histograms of the sections with normal structure had many sections with particularly large σ.
[0050] FIG. 11 shows the average peak position and average σ of a plurality of sections corresponding to the normal structure and a plurality of sections corresponding to six types of non-columnar crystal structures in an alloy for an R-T-B-based permanent magnet having a specific composition. Most of the sections corresponding to any of Structure 1a, Structure 1b, and Structures 3 to 6 had a peak position of 130 or more and 200 or less, and σ of 20 or more and 40 or less. Even when the composition of the R-T-B-based permanent magnet alloy was changed, the average peak position and average σ of each structure did not change significantly without changing the method for adjusting the brightness and contrast of the electron microscope.
[0051] The inventors have found that an R-T-B-based permanent magnet produced using an R-T-B-based permanent magnet alloy having a non-columnar crystal structure area ratio calculated using luminance analysis of 1.0% or more and 30.0% or less has good magnetic properties.
[0052] For each section for creating a luminance histogram, if the size of one section is too large, there are often two or more different structures included in the same section. If the size of one section is too small, the number of pixels included in each section decreases, resulting in a decrease in the accuracy of the luminance histogram created for each section. As a result, the peak position and σ of the luminance histogram become unclear. That is, there is an appropriate range for the size of one section depending on the type of alloy and the like.
[0053] <Composition of R-T-B-based permanent magnet alloy> There is no particular limit to the composition of the alloy for RTB permanent magnets. R represents at least one rare earth element. The rare earth elements refer to Sc, Y, and lanthanoid elements belonging to Group 3 of the long periodic table. The lanthanoid elements include, for example, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. The rare earth elements are classified into light rare earth elements and heavy rare earth elements, and the heavy rare earth elements refer to Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and the light rare earth elements are rare earth elements other than the heavy rare earth elements. In this embodiment, from the viewpoint of suitably controlling the manufacturing cost and magnetic properties, Nd and / or Pr may be included as R. In addition, from the viewpoint of improving HcJ in particular, both the light rare earth elements and the heavy rare earth elements may be included. The content of the heavy rare earth element is not particularly limited, and the heavy rare earth element may not be contained. The content of the heavy rare earth element is, for example, 5 mass % or less (including 0 mass %).
[0054] The content of R may be 29.0% by mass or more and 33.5% by mass or less. If the content of R is small, the HcJ of the resulting RTB permanent magnet tends to decrease. If the content of R is large, the Br tends to decrease.
[0055] The content of B may be 0.70% by mass or more, or 0.80% by mass or more. The upper limit of the content of B may be less than 1.0% by mass, less than 0.96% by mass, or 0.90% by mass or less. When the content of B is smaller than the stoichiometric ratio, specifically, when it is less than 1.0% by mass, the area ratio of the non-columnar crystal structure is easily set to 1.0 to 30.0%. When the content of B is small, Hk / HcJ is easily decreased. Furthermore, abnormal grain growth is easily generated when sintering at high temperatures. Furthermore, when sintering at low temperatures, Hk / HcJ is difficult to increase. When the content of B is large, abnormal grain growth is easily generated. And Br is easily decreased.
[0056] T is a transition metal element. It may be Fe alone or Fe and Co. The Co content may be 0% by mass or more and 2.0% by mass or less. The smaller the Co content, the more likely abnormal grain growth occurs when sintering at high temperatures. Also, when sintering at low temperatures, it is difficult to increase Hk / HcJ. When the Co content is large, Br and HcJ decrease. Also, the RTB permanent magnet alloy according to this embodiment tends to be expensive.
[0057] The RTB permanent magnet alloy may contain M. M is one or more selected from Cu, Ga, Zr, and Al. There is no particular limit to the total content of M. It may be 0.1% by mass or more and 2.0% by mass or less.
[0058] There is no particular limit to the Cu content. For example, it may be 0.05% by mass or more and 0.50% by mass or less. By including 0.05% by mass or more of Cu, abnormal grain growth is less likely to occur when sintering at high temperatures. In addition, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. By including 0.50% by mass or less of Cu, Br tends to be improved.
[0059] There is no particular limit to the Ga content. For example, it may be 0% by mass or more and 1.0% by mass or less. By including Ga, abnormal grain growth is less likely to occur when sintering at high temperatures. Furthermore, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. Furthermore, HcJ tends to be improved. By including 1.0% by mass or less of Ga, Br tends to be improved.
[0060] There is no particular limit to the Al content. For example, it may be 0.05% by mass or more and 1.00% by mass or less. By including 0.05% by mass or more of Al, HcJ is likely to be improved. Furthermore, even when sintering at high temperatures, abnormal grain growth is unlikely to occur. Furthermore, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. By including 1.00% by mass or less of Al, Br is likely to be improved.
[0061] There is no particular limitation on the content of Zr. For example, it may be 0.05% by mass or more and 1.00% by mass or less. By containing Zr at 0.05% by mass or more, even when sintering at a low temperature, Hk / HcJ tends to be sufficiently high. Also, when sintering at a high temperature, abnormal grain growth is less likely to occur. By containing Zr at 1.00% by mass or less, Br is likely to be improved.
[0062] The content of Fe is the substantial remainder among the components of the R-T-B-based permanent magnet alloy. That the content of Fe is the substantial remainder means the case where the total content of elements other than R, Fe, Co, B, and M is 1.0% by mass or less.
[0063] The R-T-B-based permanent magnet produced using the R-T-B-based permanent magnet alloy according to this embodiment is processed into an arbitrary shape and used. The shape of the R-T-B-based permanent magnet is not particularly limited, and for example, it can be an arbitrary shape such as a rectangular parallelepiped, hexahedron, flat plate shape, columnar shape such as a quadrangular prism, or cylindrical shape with a C-shaped cross section of the R-T-B-based permanent magnet.
[0064] Also, the R-T-B-based permanent magnet includes both a magnet product obtained by processing and magnetizing the magnet and a magnet product that has not been magnetized.
[0065] <Manufacturing method of R-T-B-based permanent magnet alloy> As an example of a method for manufacturing an R-T-B-based permanent magnet alloy, a method of manufacturing by the strip casting method using the casting apparatus shown in FIG. 12 will be described.
[0066] The casting apparatus shown in FIG. 12 has a cooling roll 21 and a tundish 23. Although not shown in FIG. 12, the casting apparatus may have components well known as components of a casting apparatus, such as a refractory crucible and a collection container. There is no particular limitation on the type of refractory crucible. For example, an alumina crucible, a mullite crucible, a zirconia crucible, etc. can be mentioned. There is no particular limitation on the material of the cooling roll 21. For example, copper, a copper alloy, a material obtained by plating or spraying on the surface of copper, a material obtained by plating or spraying on the surface of a copper alloy, etc. can be mentioned.
[0067] First, raw material metals are weighed out so as to obtain the desired alloy composition for an RTB permanent magnet alloy, and then mixed to obtain a raw material mixture.
[0068] Next, the obtained raw material mixture is loaded into a refractory crucible, and the loaded raw material mixture is melted to obtain a molten alloy. There is no particular limitation on the method for melting the raw material mixture. For example, a method of placing the refractory crucible loaded with the raw material mixture in a high-frequency vacuum induction furnace and heating it can be mentioned.
[0069] The obtained molten alloy is then cast to obtain a cast alloy ribbon (alloy for RTB permanent magnets) by a strip casting method using a casting device shown in Fig. 12. Specifically, the molten alloy 25 is supplied to a chill roll 21, the inside of which is water-cooled, via a tundish 23. The molten alloy 25 supplied onto the chill roll 21 is cooled and separated from the chill roll 21 on the opposite side of the tundish 23, and is recovered as a cast alloy ribbon.
[0070] In the cast alloy ribbon, the surface in contact with the chill roll 21 is the roll surface, and the surface opposite to the roll surface is the free surface. The roll surface is cooled by the chill roll 21 more rapidly than the free surface. Here, a non-columnar crystal structure is more likely to form when the cooling rate is faster than that of a normal crystal structure. Among non-columnar crystal structures, a chill crystal structure is more likely to form when the cooling rate is particularly fast. Therefore, the roll surface is more likely to form when compared to the free surface. Not A columnar crystal structure is easily generated. In addition, the roll surface is on the left side in all of Figures 1 to 9.
[0071] non-columnar crystal group WovenThe area ratio varies mainly depending on the temperature (casting temperature) of the molten alloy 25, the composition of the molten alloy 25, the roll surface roughness Rz of the chill roll 21, the shape of the unevenness that affects the roll surface roughness Rz, the molten metal head pressure 27, the roll circumferential speed of the chill roll 21, and the supply speed of the molten alloy 25 to the chill roll 21 (the supply speed per unit contact width between the molten alloy 25 and the chill roll 21). The temperature of the molten alloy 25 is, for example, 1300 to 1600°C. The roll surface roughness Rz of the chill roll 21 is, for example, 10 to 50 μm. The roll circumferential speed of the chill roll 21 is, for example, 0.5 to 2.5 m / s. The supply speed of the molten alloy 25 to the chill roll 21 is, for example, 0.5 to 2.5 kg / (min cm).
[0072] The molten metal head pressure 27 will be described below. The molten metal head pressure 27 refers to the depth of the molten alloy 25 in contact with the chill roll 21. The higher the molten metal head pressure 27, the stronger the pressure with which the molten alloy 25 is pressed against the chill roll 21 by its own weight. Therefore, the higher the molten metal head pressure 27, the stronger the adhesion between the molten alloy 25 and the chill roll 21 becomes, and the higher the heat transfer coefficient from the molten alloy 25 to the chill roll 21 becomes. At the same time, the length of the molten alloy 25 in contact with the chill roll 21 also changes. Therefore, if other conditions are the same, the higher the molten metal head pressure 27, the thicker the cast alloy ribbon will be. In practice, the molten metal head pressure 27 is appropriately selected in accordance with other casting conditions.
[0073] As described above, the faster the cooling rate, the more likely it is that a non-columnar structure (chilled structure) will form. Therefore, the greater the molten metal head pressure 27, the greater the area ratio of the non-columnar structure (chilled structure) tends to be.
[0074] As a method of increasing the molten metal head pressure 27, a method of increasing the amount of the alloy molten metal 25 in the tundish 23 can be mentioned. As a method of increasing the amount of the alloy molten metal 25 in the tundish 23, a method of increasing the supply rate of the alloy molten metal 25 to the tundish 23 can be mentioned. If the supply rate of the alloy molten metal 25 to the tundish 23 becomes faster, the thickness of the cast alloy ribbon will become thicker. As a method of increasing the molten metal head pressure 27 without changing the thickness of the cast alloy ribbon, a method of increasing the peripheral speed of the cooling roll 21 can be mentioned.
[0075] That is, when producing a cast alloy ribbon of the same thickness, if the supply rate of the alloy molten metal 25 is fast and the peripheral speed of the cooling roll 21 is fast, the molten metal head pressure 27 will increase. If the supply rate of the alloy molten metal 25 is slow and the peripheral speed of the cooling roll 21 is slow, the molten metal head pressure 27 will decrease.
[0076] <Method for manufacturing R-T-B-based permanent magnet> There are no particular restrictions on the method for manufacturing an R-T-B-based permanent magnet using the alloy for R-T-B-based permanent magnet manufactured by the above method. For example, a method having the following steps can be mentioned. (a) Crushing step of crushing the alloy for R-T-B-based permanent magnet (b) Molding step of molding the obtained alloy powder (c) Sintering step of sintering the molded body to obtain an R-T-B-based permanent magnet (d) Aging treatment step of aging-treating the R-T-B-based permanent magnet (e) Cooling step of cooling the R-T-B-based permanent magnet (f) Processing step of processing the R-T-B-based permanent magnet (g) Grain boundary diffusion step of diffusing a heavy rare earth element into the grain boundary of the R-T-B-based permanent magnet (h) Surface treatment step of surface-treating the R-T-B-based permanent magnet
[0077] [Crushing step] The alloy for R-T-B-based permanent magnet is crushed (crushing step). The crushing step includes a coarse crushing step of crushing until the particle size becomes about several hundred μm to several mm, and a fine crushing step of finely crushing until the particle size becomes about several μm.
[0078] (Coarse grinding process) The RTB permanent magnet alloy is coarsely pulverized until the particle size is about several hundred μm to several mm (coarse pulverization step). This produces a coarsely pulverized powder of the RTB permanent magnet alloy. The coarse pulverization can be performed, for example, by absorbing hydrogen into the RTB permanent magnet alloy, then releasing hydrogen based on the difference in the amount of hydrogen absorbed between different phases, and dehydrogenating the alloy to cause self-destructive pulverization (hydrogen absorption pulverization).
[0079] The coarse pulverization step may be performed in an inert gas atmosphere using a coarse pulverizer such as a stamp mill, a jaw crusher, or a Braun mill, other than the hydrogen absorption pulverization method described above.
[0080] The oxygen concentration is adjusted by controlling the atmosphere in each manufacturing process. From the viewpoint of obtaining high magnetic properties, the oxygen content of the finally obtained RTB permanent magnet may be reduced. To achieve this, the oxygen concentration in each process from the grinding process to the sintering process described below may be set to 100 ppm or less.
[0081] (Fine grinding process) After the RTB permanent magnet alloy is coarsely pulverized, the obtained coarsely pulverized powder of the RTB permanent magnet alloy is finely pulverized until the average particle size is about several μm (fine pulverization step). This produces finely pulverized powder of the RTB permanent magnet alloy. By further finely pulverizing the coarsely pulverized powder, finely pulverized powder having particles of, for example, 1 μm to 10 μm, or 3 μm to 5 μm can be obtained.
[0082] Fine pulverization is performed by further pulverizing the coarsely pulverized powder using a fine pulverizer such as a jet mill, ball mill, vibration mill, wet attritor, etc., while appropriately adjusting conditions such as pulverization time. A jet mill is a method in which a high-pressure inert gas (e.g., N2 gas) is released from a narrow nozzle to generate a high-speed gas flow, and this high-speed gas flow accelerates the coarsely pulverized powder of the raw alloy, causing collisions between the coarsely pulverized powder of the raw alloy and with a target or the wall of a container, thereby pulverizing the powder.
[0083] When the coarsely pulverized powder of the raw alloy is pulverized, a pulverization aid such as zinc stearate, urea, stearic acid amide, or oleic acid amide can be added to obtain a finely pulverized powder with a high degree of orientation during compaction.
[0084] [Molding process] The pulverized powder is molded into the desired shape (molding process). In the molding process, the pulverized powder is filled into a die surrounded by an electromagnet and pressurized to mold the pulverized powder into any shape. This is done while a magnetic field is applied, which creates a specific orientation in the pulverized powder, and molding is performed in the magnetic field with the crystal axes aligned. This produces a molded body. The resulting molded body is oriented in a specific direction, resulting in an RTB permanent magnet with stronger magnetic anisotropy.
[0085] The pressure during molding may be 30 MPa to 300 MPa. The magnetic field applied may be 950 kA / m to 1600 kA / m. The magnetic field applied is not limited to a static magnetic field, and may be a pulsed magnetic field. A static magnetic field and a pulsed magnetic field may also be used in combination.
[0086] As a molding method, in addition to the dry molding in which the finely pulverized powder is molded as is as described above, wet molding in which a slurry in which the finely pulverized powder is dispersed in a solvent such as oil can also be applied.
[0087] The shape of the green body obtained by compacting the finely pulverized powder is not particularly limited, and can be any shape depending on the desired shape of the RTB permanent magnet, such as a rectangular parallelepiped, flat plate, column, ring, etc.
[0088] [Sintering process] The green body obtained by molding in a magnetic field and forming into the desired shape is sintered in a vacuum or inert gas atmosphere to obtain an RTB permanent magnet (sintering process). The sintering temperature needs to be adjusted depending on various conditions such as the composition, the pulverization method, the particle size and particle size distribution, etc. The green body is sintered, for example, by heating in a vacuum or in the presence of an inert gas at 1000°C to 1200°C for 1 hour to 48 hours. This causes liquid phase sintering of the finely pulverized powder, and an RTB permanent magnet (sintered body of RTB magnet) with an increased volume ratio of main phase particles is obtained. After sintering the green body to obtain the sintered body, the sintered body may be rapidly cooled from the viewpoint of improving production efficiency.
[0089] [Aging treatment process] After sintering the compact, the RTB permanent magnet is subjected to an ageing treatment (aging treatment step). After sintering, the RTB permanent magnet is subjected to an ageing treatment by, for example, holding the obtained RTB permanent magnet at a temperature lower than that at the time of sintering. The aging treatment may be, for example, a two-stage heating at a temperature of 700°C or higher and 1000°C or lower for 10 minutes to 6 hours, and then a one-stage heating at a temperature of 500°C to 700°C for 10 minutes to 6 hours, or a one-stage heating at a temperature of about 600°C for 10 minutes to 6 hours, and the treatment conditions are appropriately adjusted depending on the number of times the aging treatment is performed. Such an aging treatment can improve the magnetic properties of the RTB permanent magnet. The aging treatment step may also be performed after the processing step described below.
[0090] [Cooling process] After the RTB permanent magnet is subjected to aging treatment, the RTB permanent magnet is rapidly cooled in an Ar gas atmosphere (cooling step). This makes it possible to obtain the RTB permanent magnet according to the present embodiment. The cooling rate is not particularly limited, and may be 30°C / min or more.
[0091] [Processing process] The obtained RTB permanent magnet may be processed into a desired shape as necessary (processing step). Examples of processing methods include shaping such as cutting and grinding, and chamfering such as barrel polishing.
[0092] [Grain boundary diffusion process] A heavy rare earth element may be further diffused into the grain boundaries of the processed RTB permanent magnet (grain boundary diffusion step). There are no particular limitations on the method of grain boundary diffusion. For example, it may be carried out by attaching a compound containing a heavy rare earth element to the surface of the RTB permanent magnet by coating or vapor deposition, etc., and then carrying out a heat treatment. It may also be carried out by carrying out a heat treatment on the RTB permanent magnet in an atmosphere containing vapor of the heavy rare earth element. Grain boundary diffusion can further improve the HcJ of the RTB permanent magnet.
[0093] [Surface treatment process] The RTB permanent magnet obtained by the above steps may be subjected to surface treatment such as plating, resin coating, oxidation treatment, chemical conversion treatment, etc. (surface treatment step).
[0094] In this embodiment, the processing step, the grain boundary diffusion step, and the surface treatment step are performed, but these steps do not necessarily have to be performed.
[0095] The RTB permanent magnet according to this embodiment obtained as described above has good magnetic properties and a wide sintering temperature range, which makes it possible to stably produce the RTB permanent magnet according to this embodiment.
[0096] The RTB permanent magnet according to this embodiment obtained in this manner is suitable for use as a magnet in, for example, a surface permanent magnet (SPM) rotating machine with a magnet attached to the rotor surface, an interior permanent magnet (IPM) rotating machine such as an inner rotor brushless motor, a permanent magnet reluctance motor (PRM), etc. Specifically, the RTB permanent magnet according to this embodiment is suitable for use in spindle motors and voice coil motors for rotating hard disks in hard disk drives, motors for electric and hybrid cars, motors for electric power steering in automobiles, servo motors for machine tools, motors for vibrators in mobile phones, motors for printers, motors for generators, etc.
[0097] The present invention is not limited to the above-described embodiment, and various modifications can be made within the scope of the present invention. EXAMPLES
[0098] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0099] (Preparation of alloys for RTB permanent magnets) Nd metal (purity 99% by mass or more), Nd-Pr alloy (didymium, purity 99% by mass or more), Tb metal (purity 99% by mass or more), ferroboron (Fe content 80% by mass, B content 20% by mass), Fe metal (purity 99% by mass or more), Co metal (purity 99% by mass or more), Zr metal (purity 99% by mass or more), Cu metal (purity 99% by mass or more), Al metal (purity 99% by mass or more), and Ga metal (purity 99% by mass or more) were weighed out to obtain the alloy composition shown in Table 1 below and mixed to obtain a raw material mixture. In Table 1, "T.RE" is the total content (mass%) of rare earth elements (Nd, Pr, Dy, and Tb), "T.RL" is the total content (mass%) of light rare earth elements (Nd and Pr). "bal." is the remainder. The Fe content is indicated as "bal." to indicate that the Fe content is the remainder when the entire RTB permanent magnet alloy, which contains elements other than the elements listed in Table 1, is taken as 100 mass %.
[0100] The obtained raw material mixture was loaded into an alumina crucible. The alumina crucible loaded with the raw material mixture was placed in a high-frequency vacuum induction furnace, and the atmosphere inside the high-frequency vacuum induction furnace was then replaced with Ar. The high-frequency vacuum induction furnace was then heated to melt the raw material mixture loaded into the alumina crucible, thereby obtaining a molten alloy. The obtained molten alloy was cast by a strip casting method using the casting device shown in Figure 12, to obtain a cast alloy ribbon (alloy for RTB-based permanent magnets). Casting was performed in an Ar atmosphere.
[0101] The temperature of the molten alloy, the roll surface roughness Rz of the chill roll, and the molten metal head pressure were appropriately selected so as to obtain the alloy for RTB rare permanent magnets shown in Table 2. Specifically, the temperature of the molten alloy (casting temperature) was selected within the range of 1300 to 1600°C, the roll surface roughness Rz of the chill roll was selected within the range of 5 to 50 μm, and the molten metal head pressure was selected within the range of 5 to 25 mm. The material of the chill roll was a copper alloy. The roll peripheral speed of the chill roll and the supply speed of the molten metal to the chill roll (supply speed per unit contact width between the molten metal and the chill roll) were adjusted to the values shown in Table 2 below.
[0102] (Adjusting the electron microscope) A cross section of the obtained RTB permanent magnet alloy was observed with an electron microscope (manufactured by JEOL Ltd.) and the brightness and contrast of the electron microscope were adjusted in preparation for calculating the area ratio of the non-columnar crystal structure by brightness analysis.
[0103] First, the obtained RTB permanent magnet alloy was heat-treated at 1000°C for 120 minutes to obtain two heat-treated plates for incorporation into standard samples.
[0104] Next, a 0.1 mm thick Ni thin plate, a 0.1 mm thick Cu thin plate, and a 0.1 mm thick Zn thin plate were prepared. Next, the heat-treated plate, Ni thin plate, Cu thin plate, and Zn thin plate were embedded in an embedding resin for electron microscope observation. At this time, the heat-treated plate, Ni thin plate, Cu thin plate, Zn thin plate, and heat-treated plate were arranged in this order so that the cross sections of each plate were parallel to the thickness direction, to prepare a standard sample.
[0105] Next, the cross section of the standard sample was mirror-polished and gold was evaporated onto it.
[0106] Next, the standard sample was set in an electron microscope. The imaging mode was set to a backscattered electron image, with a magnification of 150 and a pixel count of 1280 × 960 pixels.
[0107] Next, the field of view was adjusted so that the Ni thin plate, the Cu thin plate, and the Zn thin plate were in that order within the same field of view.
[0108] Next, a luminance histogram was created with 256 gradations, with the minimum luminance being 0 and the maximum luminance being 255, and the brightness was adjusted so that the position of the Cu luminance peak was approximately 150 (145-155). Furthermore, the contrast was adjusted so that the difference between the positions of the Ni luminance peak and the Cu luminance peak was approximately 55 (45-65), and the difference between the positions of the Cu luminance peak and the Zn luminance peak was approximately 45 (35-55). When adjusting the contrast, the brightness was additionally adjusted as necessary to maintain the position of the Cu luminance peak at approximately 150.
[0109] Next, the field of view was moved to a position where the heat-treated plate was placed while maintaining the contrast. Then, the magnification was increased so that the white phase (R-rich phase 13) was not included in the field of view and only the main phase 11 was included in the field of view. The maximum magnification was about 10,000 times. Furthermore, the brightness was adjusted so that the peak position of the brightness histogram was about 110 (105 to 115). Finally, the standard sample was collected from the electron microscope.
[0110] (Measurement of area ratio of non-columnar crystal structure) The area ratio of the non-columnar crystal structure in the RTB permanent magnet alloy was measured using an electron microscope whose brightness and contrast were adjusted by the above-mentioned method.
[0111] First, samples for evaluation were taken. Specifically, in the process in which one production lot of RTB permanent magnet alloy was supplied by the above-mentioned strip casting method, alloy flakes were sampled from the RTB permanent magnet alloy supplied at regular time intervals. Thirty alloy flakes were randomly taken from the RTB permanent magnet alloy, and each alloy flake was used as an evaluation sample.
[0112] Next, the thickness of the collected evaluation samples was measured. Of the 30 evaluation samples, the 2nd, 3rd, and 4th thickest samples were selected as thick samples, the 14th, 15th, and 16th thickest samples were selected as near average samples, and the 27th, 28th, and 29th thickest samples were selected as thin samples.
[0113] Next, the nine selected evaluation samples were attached with instant adhesive and processed so that a cross section parallel to the thickness direction could be observed. When attaching the evaluation samples, they were arranged so that it was clear which evaluation sample was a thick sample, which was a sample near the average, or which was a thin sample.
[0114] Next, the nine evaluation samples attached with instant adhesive were embedded in resin together to form one embedded resin sample. The cross section parallel to the thickness direction was then mirror-finished to prepare an observation surface.
[0115] Next, the imaging mode was a backscattered electron image, the magnification was 350 times, and the number of pixels was 1280 × 960 pixels, and the observation range was set. The observation range was selected from the observation surface of each evaluation sample in an average state. Next, the area ratio of the non-columnar crystal structure in the observation range was calculated by analysis.
[0116] The specific analysis procedure is explained below. First, the above observation range was divided into sections at regular intervals. Each section had a dimension of 50 pixels.
[0117] Next, a luminance histogram was created for each section, and the peak position and σ of the luminance histogram were obtained for each section.
[0118] Next, each section was judged as to whether it was a non-columnar crystal structure. Specifically, a section in which the peak position of the brightness histogram was 130 or more and 200 or less, and σ was 20 or more and 40 or less, was deemed to be a non-columnar crystal structure. A section in which the peak position of the brightness histogram or σ was outside the above range was deemed not to be a non-columnar crystal structure. Each section in the observation range was judged as to whether it was a non-columnar crystal structure, and the number of sections in the observation range that were non-columnar crystal structures was divided by the number of all sections to determine the area ratio of the non-columnar crystal structure in the cross section of each evaluation sample.
[0119] The area ratio of the non-columnar crystal structure in the cross section of each evaluation sample was then averaged to calculate the area ratio of the non-columnar crystal structure in the cross section of one production lot of the RTB permanent magnet alloy. The results are shown in Table 2.
[0120] (Production of RTB permanent magnets) After hydrogen was absorbed into the RTB permanent magnet alloy at room temperature, hydrogen was removed in a vacuum at 600°C for 1 hour (coarse pulverization) to obtain an alloy powder (coarse pulverized powder). In this example, each step from the hydrogen pulverization to sintering (fine pulverization and molding) was carried out in an Ar atmosphere with an oxygen concentration of less than 50 ppm or in a vacuum.
[0121] Next, zinc stearate and stearic acid amide were added to the alloy powder as grinding aids and mixed using a Nauta mixer. The amount of zinc stearate added was 0.05 parts by mass per 100 parts by mass of the coarsely ground powder. The amount of stearic acid amide added was 0.05 parts by mass per 100 parts by mass of the coarsely ground powder. Then, fine grinding was performed using a jet mill to obtain a finely ground powder with an average particle size of about 3.0 μm.
[0122] The resulting finely pulverized powder was filled into a die placed in an electromagnet, and compacted in a magnetic field by applying a pressure of 120 MPa while applying a magnetic field of 1200 kA / m to the die, to obtain a compact.
[0123] The obtained green body was then sintered by holding it in a vacuum at 1,050°C for 4 hours and then rapidly cooled to obtain a sintered body having the magnet composition shown in Table 1. The obtained sintered body was then subjected to a two-stage aging treatment at 900°C for 1 hour and at 500°C for 1 hour (both in an Ar atmosphere) to obtain an RTB-based permanent magnet (RTB-based sintered magnet).
[0124] [Magnetic properties] The Br, HcJ and Hk / HcJ of each sample were measured using a BH tracer. Br was measured at room temperature for all samples. In Examples 1 to 4 and Comparative Example 1, HcJ and Hk / HcJ were measured at room temperature. In the other Examples and Comparative Examples, HcJ and Hk / HcJ were measured at 150°C. Note that Hk in this example is the value of the magnetic field when the magnetization is Br x 0.9 in the second quadrant of the demagnetization curve.
[0125] [Table 1]
[0126] [Table 2]
[0127] From Examples 1 to 4 and Comparative Example 1, the RTB permanent magnets of Examples 1 to 4, which were produced using alloys for RTB permanent magnets in which the area ratio of the non-columnar crystal structure was 1.0% or more and 30.0% or less, had higher Br, comparable HcJ, and higher Hk / HcJ than the RTB permanent magnet of Comparative Example 1, which was produced using an alloy for RTB permanent magnets produced under the same conditions except that the area ratio of the non-columnar crystal structure was outside the above range. In particular, the Hk / HcJ at room temperature was higher.
[0128] From Examples 5 to 11, the RTB permanent magnets of Examples 6 to 11, which were produced using alloys for RTB permanent magnets in which the area ratio of the non-columnar crystal structure was 4.0% or more and 30.0% or less, had higher HcJ than Example 5, which was produced under the same conditions except that the area ratio of the non-columnar crystal structure was 1.0% or more and less than 4.0%.
[0129] From Examples 6 to 11, it was found that the RTB permanent magnets produced under the same conditions except that the area ratio of the non-columnar crystal structure in the RTB permanent magnet alloy was changed from 4.0% to 30.0% showed a tendency for the HcJ to increase as the area ratio of the non-columnar crystal structure in the RTB permanent magnet alloy increased.
[0130] In Comparative Example 2, the B content was 0.96 mass%, which was higher than the other Examples. Therefore, even under casting conditions similar to those of the other Examples, the area ratio of the non-columnar crystal structure was reduced. As a result, the HcJ was reduced compared to the Examples.
[0131] In addition, it was confirmed that in all the examples, the area ratio of structures other than chilled crystal structures in the non-columnar crystal structure was 85% or more and 95% or less. [Explanation of symbols]
[0132] 1...Chill crystal structure 3...Microscopic dotted R-rich phase-containing structure 4…Punctate R-rich phase-containing structure 5...Micro-linear R-rich phase-containing structure 6...Large dot-like R-rich phase-containing structure 7…Normal organization 11…Main phase 13…R-rich phase 21...Cooling roll 23…Tundish 25…Molten alloy 27…Molten metal head pressure
Claims
1. An R-T-B system alloy for a permanent magnet having R, T and B, where R is a rare earth element, T is a transition metal element and B is boron, the area ratio of a non-columnar crystal structure in a cross section being 1.0% or more and 30.0% or less, The non-columnar crystal structure contains a chilled crystal structure, and the area ratio of structures other than the chilled crystal structure in the non-columnar crystal structure is 85% or more and 95% or less.
2. An R-T-B system alloy for a permanent magnet having R, T and B, where R is a rare earth element, T is a transition metal element and B is boron, the area ratio of a non-columnar crystal structure in a cross section being 1.0% or more and 30.0% or less, An R-T-B based alloy for permanent magnets, having an R content of 29.0 mass % or more and 33.5 mass % or less, and a B content of 0.70 mass % or more and less than 0.96 mass %.
3. 3. An RTB system alloy for permanent magnets according to claim 1, wherein the area ratio of the non-columnar crystal structure is 4.0% or more and 30.0% or less.
4. 4. An R-T-B system permanent magnet alloy according to claim 2, wherein the non-columnar crystal structure contains a chilled crystal structure, and an area ratio of structures other than the chilled crystal structure in the non-columnar crystal structure is 50% or more.
5. 5. An R-T-B system alloy for permanent magnets according to claim 1, 3 or 4, wherein the R content is 29.0 mass % or more and 33.5 mass % or less, and the B content is 0.70 mass % or more and less than 0.96 mass %.
6. A method for producing an RTB system permanent magnet, comprising the step of pulverizing the RTB system permanent magnet alloy according to any one of claims 1 to 5.
Citation Information
Patent Citations
Alloy thin strip for rare earth magnet, alloy fine powder and their production
JP2000219942A
Alloy thin strip for rare earth magnet, alloy fine powder and their production
JP2000219943A
Rare earth magnetic alloy sheet, its manufacturing method, sintered rare earth magnetic alloy powder, sintered rare earth magnet, metal powder for bonded magnet, and bonded magnet
JP2003188006A
Method for producing rare-earth containing alloy flake, alloy flake for rare-earth magnet, alloy powder for rare-earth sintered magnet, rare-earth sintered magnet, alloy powder for bonded magnet and bonded magnet, and evaluation method for metallic structure
JP2004181531A
Rare earth alloy cast sheet and method for producing the same
JP2008264875A